PENGARUH PENGGUNAAN MEDIA WEB COOLMATH4KIDS TERHADAP KEMAMPUAN BERHITUNG CEPAT MATEMATIKA SISWA KELAS II SD MUHAMMADIYAH PERUMNAS - Resita, Reza; Baharullah, Baharullah; Syam, Haerul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The aim of this study is to determine the effect of the coolmath4kids website on the mathematical quick calculation ability of students in the second grade at SD Muhammadiyah Perumnas, Makassar. The research problem in this study is whether there is an effect of using the coolmath4kids website on the ability of students in the second grade at SD Muhammadiyah Perumnas to calculate quickly. The study used a quantitative approach with a pre-experimental design and a one-group pretest-posttest design. The population in this study is all the students in Year 2 at SD Muhammadiyah Perumnas, with a sample of 23 students selected using the total sampling technique. Data was collected through a learning outcomes test given before (pre-test) and after (post-test) the intervention. The research instrument was a learning outcome test (pretest and posttest) as well as a sheet to observe student activity. Data analysis techniques used statistic descriptive and inferential with the help of SPSS 25. The data normality test was performed using the Shapiro-Wilk test, which showed that the pretest and posttest data were normally distributed. The hypothesis test used was paired sample t-test. The results of the study showed an increase in the average score from 51.13 (pre-test) to 89.35 (post-test). The paired samples t-test showed a significance value of 0.000 < 0.05, meaning that H0 was rejected and H1 was accepted. It can therefore be concluded that the use of the web media coolmath4kids has a significant impact on students' ability to quickly calculate in class II at SD Muhammadiyah Perumnas.